CLINICAL FEATURES OF THE COURSE OF CHRONIC PHARYNGITIS ASSOCIATED WITH LARYNGOPHARYNGEAL REFLUX (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
Chronic pharyngitis (CP) is one of the most common inflammatory diseases of the upper respiratory tract, characterized by persistent complaints of throat irritation, dryness, cough, and a “lump in the throat” sensation. In recent years, laryngopharyngeal reflux (LPR) has attracted increasing attention as an important pathogenetic factor in chronic inflammation of the pharyngeal mucosa. The aim of this article is to summarize current data on the clinical manifestations and diagnosis of CP associated with LPR, based on an analysis of international publications from 2024–2025.